Urgensi Religiusitas dan Moral Untuk Membangun Sikap Toleransi dalam Perspektif Konseling Lintas Agama - Ihda Riezma Farhania; Zulkipli Lessy (CV. ULIL ALBAB CORP, 2024)
Harmony and tolerance are valuable resources for building a country with strong defense. In some cases, social conflict is something that is difficult to avoid. The study of interfaith guidance and counseling has the basic assumption of building sustainable harmony as a preventive effort in reducing conflicts that occur in social life. In essence, someone who knows religion will have high moral values ​​within themselves. This is the basis for building social ethics and tolerance. This research uses a qualitative method with a literature approach using description techniques and data collection from various reference books, journals and previous research articles which provide an overview of the concept of tolerance in interfaith counseling. The results to be achieved in this research are a description of the urgency of moral values ​​and religiosity in building an attitude of tolerance which is studied from an interfaith counseling perspective.